Kidnapping in Cameron Glen - Cornelison, Beth (Cornelison, Beth. Cameron Glen, 2022)
"Jake and Emma Turner's marriage is in ruins. Their latest shouting match has driven their teenage daughter to run away from home. But when evidence surfaces that she's been kidnapped by human traffickers, the couple must set aside their conflicts to save their child. With time running out, can the pair's desperation bring them together...now and forever?"--Back cover.